2012
DOI: 10.1016/j.iheduc.2011.05.008
|View full text |Cite
|
Sign up to set email alerts
|

“Actually, I Wanted to Learn”: Study-related knowledge exchange on social networking sites

Abstract: Resumen. La incorporación a la educación superior de herramientas como plataformas virtuales o redes sociales supone una nueva reformulación del proceso de enseñanza-aprendizaje. Esta investigación analiza la utilidad didáctico-pedagógica de la plataforma educativa Moodle y de la red social Facebook para identificar sus potencialidades y controversias. Se presenta un estudio descriptivo e interpretativo que combina el diseño cualitativo y cuantitativo, para conocer la opinión del profesorado y alumnado

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0
14

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(88 citation statements)
references
References 26 publications
5
69
0
14
Order By: Relevance
“…This view is supported by the result reported in related literature that courses involving cooperative learning contribute to learning (Al-Rahmi & Othman, 2013;Biasutti, 2011;Ekici & Kiyici, 2012;Forkosh-Baruch & Hershkovitz, 2012;Grosseck et al, 2011;Hung & Yuen, 2010;R. Junco et al, 2011;Kabilan et al, 2010;Lawson et al, 2011;Mazer et al, 2007Mazer et al, , 2009Wodzicki et al, 2012). Despite all these positive views, there were some other students with negative views who reported that it took quite a lot of time for them to carry out the activities involving cooperative learning.…”
Section: Conclusion Discussion and Suggestionssupporting
confidence: 57%
“…This view is supported by the result reported in related literature that courses involving cooperative learning contribute to learning (Al-Rahmi & Othman, 2013;Biasutti, 2011;Ekici & Kiyici, 2012;Forkosh-Baruch & Hershkovitz, 2012;Grosseck et al, 2011;Hung & Yuen, 2010;R. Junco et al, 2011;Kabilan et al, 2010;Lawson et al, 2011;Mazer et al, 2007Mazer et al, , 2009Wodzicki et al, 2012). Despite all these positive views, there were some other students with negative views who reported that it took quite a lot of time for them to carry out the activities involving cooperative learning.…”
Section: Conclusion Discussion and Suggestionssupporting
confidence: 57%
“…These findings are almost correspondent to the results of recent studies (Lin & Lu, 2011;Wodzicki, Schwämmlein, & Moskaliuk, 2011). In addition, there are many proofs that college students use SNSs technology for getting a positive effect of socialization at universities and social learning outcomes (Lin & Lu, 2011;Nadkarni & Hofmann, 2012;Wodzicki, Schwämmlein, & Moskaliuk, 2011). Secondly, using SNSs is still limited for specific purposes in higher education, such as discussing courses related topics with students, sharing educational resources, and asking questions, because there are limited regulated learning environments to blend SNSs as a part of e-learning or traditional classes.…”
Section: Discussionsupporting
confidence: 92%
“…Firstly, most of the scholars agreed that youth use SNSs technology for supporting emotions, to feel free and to improve their social life. These findings are almost correspondent to the results of recent studies (Lin & Lu, 2011;Wodzicki, Schwämmlein, & Moskaliuk, 2011). In addition, there are many proofs that college students use SNSs technology for getting a positive effect of socialization at universities and social learning outcomes (Lin & Lu, 2011;Nadkarni & Hofmann, 2012;Wodzicki, Schwämmlein, & Moskaliuk, 2011).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…For example, researchers have examined local SNS created to help transition incoming freshmen into their college careers (DeAndrea, Ellison, LaRose, Steinfield, & Flore, 2012), investigated the sharing of school-related knowledge on online social networks (Wodzicki, Schwämmiein, & Moskaliuk, 2012), explored the use of online social networks by faculty (Kaya, 2010), and studied the integration of social networking environments in traditional higher education settings (Veletsianos, Kimmons, & French, 2013).…”
mentioning
confidence: 99%